Optimal design in pediatric pharmacokinetic and pharmacodynamic clinical studies. Issue 3 (9th January 2015) - Roberts, Jessica K.; Stockmann, Chris; Balch, Alfred; Yu, Tian; Ward, Robert M.; Spigarelli, Michael G.; Sherwin, Catherine M. T.; Anderson, Brian
Summary It is not trivial to conduct clinical trials with pediatric participants. Ethical, logistical, and financial considerations add to the complexity of pediatric studies. Optimal design theory allows investigators the opportunity to apply mathematical optimization algorithms to define how to structure their data collection to answer focused research questions. These techniques can be used to determine an optimal sample size, optimal sample times, and the number of samples required for pharmacokinetic and pharmacodynamic studies. The aim of this review is to demonstrate how to determine optimal sample size, optimal sample times, and the number of samples required from each patient by presenting specific examples using optimal design tools. Additionally, this review aims to discuss the relative usefulness of sparse vs rich data. This review is intended to educate the clinician, as well as the basic research scientist, whom plan on conducting a pharmacokinetic/pharmacodynamic clinical trial in pediatric patients.